2008
DOI: 10.1088/0960-1317/18/7/075034
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ‘bi-layer lift-off’ method for high flow rate and high frequency Nitinol MEMS valve fabrication

Abstract: This paper presents modeling, fabrication and testing results for a high flow rate and high frequency nickel titanium alloy (Nitinol) MEMS valve. ANSYS R is used to evaluate several Nitinol MEMS valve structural designs with the conclusion that a pentagonal flap with five legs produces higher frequencies and higher strengths without the inherent rotation problem present in four-leg designs. The Nitinol penta-leg design was fabricated using a novel bi-layer lift-off method. A polymethylglutarimide (PMGI) polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The measured flow rates from the miniature-reed valves are lower than the flow rates for the single-reed valves, but this is expected because the miniature-reed array design utilizes the existing valve ports at a penalty of greatly reduced available flow area. The flow restriction of the valves could be reduced simply by using a larger number of valves in the array (Lee et al, 2007; Li and Chen, 2005; Seong et al, 2008). The area of the pump piston is approximately eight times the area of the inlet and outlet reeds combined (507 mm 2 vs. 63 mm 2 ), so a pump designed specifically for a miniature-reed array could utilize significantly more valves without increasing the overall size of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured flow rates from the miniature-reed valves are lower than the flow rates for the single-reed valves, but this is expected because the miniature-reed array design utilizes the existing valve ports at a penalty of greatly reduced available flow area. The flow restriction of the valves could be reduced simply by using a larger number of valves in the array (Lee et al, 2007; Li and Chen, 2005; Seong et al, 2008). The area of the pump piston is approximately eight times the area of the inlet and outlet reeds combined (507 mm 2 vs. 63 mm 2 ), so a pump designed specifically for a miniature-reed array could utilize significantly more valves without increasing the overall size of the system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the silicon valves were found to quickly fail when tested at pump pressures, and the nickel valves produced unacceptably high reverse flows because of fabrication defects (O’Neill and Burchfield, 2007). Seong et al (2008) used nitinol to design a miniature valve array with large valve openings by taking advantage of the high strains (up to 10%) available due to the pseudoelastic effect. Testing was limited to static flow conditions; fatigue-life considerations may limit the available strains from nitinol for high-frequency pump applications (Eggeler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Other work has included the development of miniature check valve arrays, which exhibit higher resonance frequencies by virtue of the reduced mass of the individual valves. [13][14][15][16] Recent work by the authors demonstrated that the miniature valve approach can successfully rectify flow; however, the overall actuator bandwidth remains limited by the pump manifold design. 17 We investigate the effect of the fluid passages in the pumping manifold on the overall bandwidth of the actuator.…”
Section: Introductionmentioning
confidence: 99%
“…shape memory effect) up to 10% due to twin boundary motion when it transforms between martensite and austenite phases. Due to the shape memory effect, many researchers have used NiTi in various actuator and sensor applications including MEMS devices [13][14][15][16][17]. However, controlling wrinkles with NiTi thin film has not been previously investigated and an attempt has not been made for in situ wrinkle control.…”
Section: Introductionmentioning
confidence: 99%